PENGGUNAAN DIKSI DAN GAYA BAHASA DALAM PENULISAN CERITA PENDEK SISWA KELAS IX SMP NEGERI 1 SUNGAI RAYA - Dayanti, I'is; Priyadi, Antonius Totok; Muzammil, Ahmad Rabiul (Universitas Tanjungpura, 2024)
This research discusses the problem of the use of diction and language style in the writing of short stories of class IX students of SMP Negeri 1 Sungai Raya. The purpose of the research is to describe the use of diction based on its meaning, lexical, and language style in the writing of short stories of grade IX students of SMP Negeri 1 Sungai Raya. The method used is descriptive method in qualitative form. The data source of this research is the ninth grade students of SMP Negeri 1 Sungai Raya. Data collection techniques used written test techniques with observation, assignment, field survey, data retrieval, and documentation. The research resulted in the use of diction based on its meaning, namely: denotative as many as 13 students while connotative as many as 22 students, the use of diction based on lexical as many as 14 students in the form of synonyms and as many as 18 students in the form of antonyms, while language styles were used as many as three language styles, namely: comparison, affirmation, and opposition in writing short stories of 32 students in class IX E.